Use of plyometric trainings in physical rehabilitation of athletes in playing sports with injuries of the capsule-ligament apparatus of knee - Moh'd Khalil Moh'd Abdel Kader; Parish Mohammad Reza; Nikanorov A.K (Kharkov National Pedagogical University, 2012)
The question of possibility of application is considered in the programs of physical rehabilitation of the special physical exercises for the athletes in playing sports with the damage of knee-joint. An analysis and generalization of scientific-methodical information on questions of mechanisms and features of origin of sporting traumas, and also modern facilities and methods of renewal at the traumas of the capsule-ligament apparatus of knee is conducted. It is set that in the modern methods of physical rehabilitation of sportsmen with the traumas of locomotorium the complex programs do not meet with the use of plyometric exercises. Their application is instrumental in the prophylaxis of origin of recurrent sporting traumas, renewal of the special capacity and speed-power qualities of athletes.